Learning the Qur'an through the Adz Dzikr method to facilitate the process of reading students - Khoiriyah, Siti Nur; Maruf , Achmad (International Journal of Research in Counseling, 2023)
Learning the Qur'an is an obligation for every Muslim, because people who master the Qur'an are people of knowledge, whatever interaction is carried out with the Qur'an will get rewards. One of the important things that must be considered in learning the Qur'an is the learning method, because the method is a supporting factor in order to achieve optimal learning goals, but the method used must also affect the success of the student learning process, because if the method used is not right it will result in wasted time. Based on the observations made by researchers that the method used previously was too heavy to be applied for both teachers and students, therefore teachers at TPQ Nurul Jannah tried to implement the Adz Dzikr method by adjusting the conditions of students at TPQ Nurul Jannah. The method in this study uses qualitative descriptive. Based on the results of observations, interviews and documentation conducted by this researcher, it shows that the Adz Dzikr method at TPQ Nurul Jannah is carried out using volumes 1 to 5, starting from the most basic thing, namely the introduction of hijaiyah letters to the application of reading according to the rules of tajweed, using classical strategies, classical reading listen, individually.